Design of Efficiently Encodable Moderate-Length High-Rate Irregular LDPC Codes (IEEE transactions on communications, 2004)
This paper presents a new class of irregular low-density parity-check (LDPC) codes of the moderate length (10^3le n le 10^4) and high rate (R ge 3/4) . Codes in this class admit low-complexity encoding and have lower error-rate floors than other irregular LDPC code design approaches. It is also shown that this class of LDPC codes is equivalent to a class of systematic serial turbo codes, and is an extension of irregular repeat-accumulate codes. A code design algorithm based on the combination of density evolution and differential evolution optimization with a modified cost function is presented. Moderate-length, high-rate codes with no error-rate floors down to a bit-error rate of 10^-9 are presented. Although our focus is on moderate-length, high-rate codes, the proposed coding scheme is applicable to irregular LDPC codes with other lengths and rates.